TiO2 nanoparticles decorated on BiOCl flakes with enhanced visible light photocatalytic activity - Shinde, Deepali S.; Bhange, Pallavi D.; Jha, Ratnesh K.; Bhange, Deu S. (ChemistrySelect, 2020)
Facile preparation route for BiOCl and BiOCl/TiO2 nanocomposites with TiO2 nanoparticles decorated on BiOCl flakes via solution combustion method is reported in the present paper. Structural, textural and optical properties of the prepared materials are extensively studied using various physicochemical characterization tools such as X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), UV-vis spectroscopy (DRS), N-2 adsorption-desorption study (BET), photoluminescence spectroscopy (PL), etc. BiOCl/TiO2 nanocomposites show a red shift in the light absorption as compared to that of bare BiOCl which leads to the extended absorption in visible light region. Further photocatalytic experiments for Rhodamine B and phenol degradation demonstrate that the BiOCl/TiO2 nanocomposites have superior photocatalytic properties than bare BiOCl. Improved photocatalytic performance of BiOCl/TiO2 composites is attributed to the synergistic effect between BiOCl flakes and TiO2 nanoparticles, extended visible light absorption and delayed charge recombination.
Keywords: BiOCl; Hydoxyl radical evaluation; p-n heterojunction; phenol degradation; Photocatalysis; TiO2 nanocomposites